Inspiring pro-conservation behavior through innovations in zoo exhibit and campaign design - Kelly, Ashley (Kansas State University, 2018)
… Amid rapidly increasing anthropogenically caused wildlife extinctions, zoos are often expected to embrace the role of proactive conservation organizations. Many are leading the way through innovations in the development of engaging visitor experiences. This paper evaluates the effectiveness of the new and cutting-edge immersive interpretation within the TigerTrek Exhibit at Taronga Zoo (Sydney, Australia), for its ability to influence visitors to engage in pro-conservation behaviors related to certified sustainable palm oil advocacy and consumerism. Survey data were collected from zoo visitors prior to entering the Sumatran Tiger Trek exhibit (n = 514), upon exiting the exhibit (n = 509), and by email at six-week (n = 106) and six-month (n = 18) intervals post-visit to investigate the immediate and long-term impacts of the exhibit on visitors’ pro-conservation behavioral intentions and actual behaviors. Results indicate an increase in post-visit respondents’ levels of awareness (χ² = 65.26 (1), p < .001), motivation (t = -6.976 (1029), p < .000) and behavior intentions (t = -5.256 (1042), p < .000), however, post-visit respondents also reported increased levels of concern that all palm oil is grown unsustainably (χ2 = 9.09 (1), p < .01), which runs contrary to interpretive messaging. Follow up surveys revealed after both six-weeks and six-months post-visit; 29.2% of respondents purchased a product because it contained Certified Sustainable Palm Oil, however, 50% of six-week respondents had actively avoided buying a product because it contained palm oil. By understanding how visitors perceive the interpretive messaging within an exhibit and appreciating the types of conservation behaviors visitors are willing and able to engage in, zoos can more effectively achieve their conservation campaign goals.
Keywords: Conservation; Wildlife; Tiger; Palm oil; Environmental education; Zoo interpretation